Pengaruh Ukuran Berat Benih Terhadap Perkecambahan Benih Merbau Darat (Intsia Palembanica) - Windi Wulandari; Afif Bintoro; Duryat Duryat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
The demand of mirabow wood is increasing nowdays, where as the existence species in the nature is getting reduced. Therefore, it's preservation efforts are urgent to be done. Seed size was correlated with it's vigor, where heavy seeds relatively have a better vigor, compare to the light one. The research was aimed to determine the effect of seed size to percentage of germination, average days to germinate, germination value and germination power of mirabow seeds. The research was conducted in greenhouse of Agriculture Faculty Lampung University on November 2013 to January 2014. The research was arranged in Complete Random Design (CRD), with 3 treatments and 4 replications. Seed are classified based on the weight of seed is heavy weight, medium weight, and light weight. Each unit of experiments was used 100 mirabow seeds. The observed variables were consisted of germination percentage, average day to germination, germination value, and germination power. Data analysis methods used were homogeneity of variance, variance analysis, and least significant of difference test at 5% significant level. The results showed that seed size of mirabow has a positive effect to the germination. The heavy weight of seed (> 3.49 grams) gave a better response for germination percentage 80.250% and germination value 1.595 %/day compared with the medium weight (2.36–43.49 grams) and light weight (< 2.36 grams). Keywords: germination, mirabow, seed size